Problem-solving skills training for mothers of children recently diagnosed with autism spectrum disorder: A pilot feasibility study - Nguyen, Cathina T; Fairclough, Diane L; Noll, Robert B (Autism : the international journal of research and practice, 2016)
Problem-solving skills training is an intervention designed to teach coping skills that has shown to decrease negative affectivity (depressive symptoms, negative mood, and post-traumatic stress symptoms) in mothers of children with cancer. The objective of this study was to see whether mothers of children recently diagnosed with autism spectrum disorder would be receptive to receiving problem-solving skills training (feasibility trial). Participants were recruited from a local outpatient developmental clinic that is part of a university department of pediatrics. Participants were to receive eight 1-h sessions of problem-solving skills training and were asked to complete assessments prior to beginning problem-solving skills training (T1), immediately after intervention (T2), and 3 months after T2 (T3). Outcome measures assessed problem-solving skills and negative affectivity (i.e. distress). In total, 30 mothers were approached and 24 agreed to participate (80.0%). Of them, 17 mothers completed problem-solving skills training (retention rate: 70.8%). Mothers of children with autism spectrum disorder who completed problem-solving skills training had significant decreases in negative affectivity and increases in problem-solving skills. A comparison to mothers of children with cancer shows that mothers of children with autism spectrum disorder displayed similar levels of depressive symptoms but less negative mood and fewer symptoms of post-traumatic stress. Data suggest that problem-solving skills training may be an effective way to alleviate distress in mothers of children recently diagnosed with autism spectrum disorder. Data also suggest that mothers of children with autism spectrum disorder were moderately receptive to receiving problem-solving skills training. Implications are that problem-solving skills training may be beneficial to parents of children with autism spectrum disorder; modifications to improve retention rates are suggested.